2012
DOI: 10.1179/1743294411y.0000000045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PEO power modes on structure and corrosion resistance of ceramic coatings on AZ91D Mg alloy

Abstract: The aim of this work is to investigate the effects of different power modes [constant current (CC), constant voltage (CV) and constant power (CP)] on the structure and corrosion resistance of the plasma electrolytic oxidation ceramic coatings containing Ca and P on AZ91D Mg alloy. The phase composition, morphology and element distribution of the coatings were studied by X-ray diffraction, scanning electron microscopy and energy dispersive spectroscopy. The corrosion resistance of the coatings in the simulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…All the coatings were observed to have a wavy-jagged interface with the substrate, which is most likely as a result of the dissolution of the substrate in the early stage of the PEO process. 21,22 The coating obtained at low current density was more compact and the coatings produced at higher current density had a higher degree of microcracks. The development of such defects in the PEO coatings is attributed to the thermal stresses during PEO process as a result of melting and solidification of hard ceramic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…All the coatings were observed to have a wavy-jagged interface with the substrate, which is most likely as a result of the dissolution of the substrate in the early stage of the PEO process. 21,22 The coating obtained at low current density was more compact and the coatings produced at higher current density had a higher degree of microcracks. The development of such defects in the PEO coatings is attributed to the thermal stresses during PEO process as a result of melting and solidification of hard ceramic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of this type are described at various points in Section 'Discharge characteristics', but this review does not encompass detailed consideration of exactly how the electrical power supply can be controlled during PEO processing. Information of this type is available in the literature [23][24][25][26].…”
Section: Electrical Conditionsmentioning
confidence: 99%
“…Our group has previously completed research on the growth mechanism at low-current (Chen et al, 2015). In previous works, it can be found that the structure of these coatings and the voltage curve would change significantly as time goes by (Jiang et al, 2013;Yao et al, 2013;Dehnavi et al, 2015;Sobrinho et al, 2017). Although it is easy to calculate and control the energy consumption using the constant current mode, too much energy input can cause these coatings to peel off during the final repairing stage.…”
Section: Introductionmentioning
confidence: 99%